2022
DOI: 10.1007/s10745-022-00359-9
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Knowledge, Aspiration, and Potential Application in Contemporary Fire Mitigation in Southwest Australia

Abstract: Protection of biodiversity, human assets, and cultural heritage pose significant challenges to contemporary planning of bushfire mitigation activities. Current mitigation approaches are not always appropriate, and mismanagement is a source of distress for Indigenous peoples. Increased understanding of Indigenous fire knowledge and increased Indigenous participation may provide insight into more appropriate and inclusive land management for fire mitigation. We analysed contemporary Noongar and Western fire prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Regular burning by First Nations People was one of the factors that influenced the occurrence of grassland cover and other kinds of structurally open treed environments (e.g., Bowman, 1999; Foreman, 2020). In other areas, First Nations traditions and ecological dynamics suggest that forest understoreys were likely kept open through fire exclusion, facilitating natural self‐thinning that occurs in the absence of disturbance (e.g., Gosper et al., 2013; Lamont, 1985; Rodrigues et al., 2022; Specht & Morgan, 1981; Zylstra et al., 2022, 2023). Here, using ecological and historical evidence (see Table 1), we have shown that at the time of the British invasion, the Mountain Ash forests across many areas of mainland south‐eastern Australia (and especially in the Central Highlands of Victoria) were highly unlikely to be open and park‐like.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regular burning by First Nations People was one of the factors that influenced the occurrence of grassland cover and other kinds of structurally open treed environments (e.g., Bowman, 1999; Foreman, 2020). In other areas, First Nations traditions and ecological dynamics suggest that forest understoreys were likely kept open through fire exclusion, facilitating natural self‐thinning that occurs in the absence of disturbance (e.g., Gosper et al., 2013; Lamont, 1985; Rodrigues et al., 2022; Specht & Morgan, 1981; Zylstra et al., 2022, 2023). Here, using ecological and historical evidence (see Table 1), we have shown that at the time of the British invasion, the Mountain Ash forests across many areas of mainland south‐eastern Australia (and especially in the Central Highlands of Victoria) were highly unlikely to be open and park‐like.…”
Section: Discussionmentioning
confidence: 99%
“…Regular burning by First Nations People was one of the factors that influenced the occurrence of grassland cover and other kinds of structurally open treed environments (e.g., Bowman, 1999;Foreman, 2020). In other areas, First Nations traditions and ecological dynamics suggest that forest understoreys were likely kept open through fire exclusion, facilitating natural self-thinning that occurs in the absence of disturbance (e.g., Gosper et al, 2013;Lamont, 1985;Rodrigues et al, 2022;Specht & Morgan, 1981;Zylstra et al, 2022Zylstra et al, , 2023. Here, using ecological and historical evidence (see Table 1), we have shown that at the time of the British invasion, the Mountain Ash forests across many areas of mainland , Bowd, Banks, et al (2021), See Figure 4 Early paintings Early artwork shows large trees, multi-aged stands and a dense wet understorey See Figures 7 and 8 Early photographs Early photographs show stands comprising large trees, multiaged stands and a dense, wet understorey See Figure 6 Historical accounts Old growth trees predominate, movement in the forest difficult, "domino approaches to forest clearing" Forests Commission of Victoria (1928), Hateley (2014), Noble (1976), Elms (1920) and Collett (1994) First Nations…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reptiles are an important First Nations food source across Australia, and hunting methods vary, including burning spinifex to catch fleeing animals and digging out holes occupied by burrowing species (Bird et al 2013). Burning is unlikely directly linked to use of lizard traps, as Noongar Peoples mostly avoid lighting fires on granites (Lullfitz et al 2021; Rodrigues et al 2022). Analysis into the shape and size of lizard traps, combined with documentation of TEK across their distribution, may elucidate if lizard traps vary across climate gradients and reptile species assemblages, and whether there is spatial variation in the use of lizard traps by people and reptiles.…”
Section: Discussionmentioning
confidence: 99%
“…comm., 2020; Knapp, pers. comm., 2017; Lullfitz et al 2021; Rodrigues et al 2022). Noongar-made features found on granite outcrops include augmented gnamma (rock pools), standing stones, rock art, grinding patches, and stone arrangements that provide shelter for reptiles (Bindon 1997; Guilfoyle et al 2013; Mitchell 2016), some of which are examples of human niche construction (Kendal et al 2011; Lullfitz et al 2017; Smith 2011).…”
Section: Introductionmentioning
confidence: 99%